Occurrence of rabies virus in the medulla and medulla oblongata from naturally infected horses and the absence of the virus in other regions of the central nervous system and other tissues - Silva, Renato Augusto da; Silva, Norma Moraes da; Menezes, Paulo Roberto Valadão (Pesquisa Agropecuaria Brasileira, 2014)
Two cases of naturally occurring rabies infection in mares, with the occurrence of the rabies virus only in the medulla of one and in the medulla oblongata of the other, are reported. This is of interest for the pathogenesis and diagnosis of rabies. The laboratory methods utilized were: histochemistry (Faraco), inoculation of mice and fluorescent antibody test.